First record of Bouvieraxius keiensis Sakai, 1992 and Manaxius aurantiaca n. sp. (Decapoda: Axiidea) from the waters around the Ogasawara Islands, Japan - Komai, Tomoyuki (Zootaxa, 2020)
Two species of axiid shrimp are reported from sublittoral to upper bathyal waters around the Ogasawara Islands, Japan. The first, Bouvieraxius keiensis Sakai, 1992, is recorded from Japanese waters for the first time, although it is known widely from the southwestern Pacific to western Indian Ocean. Taxonomic problems of this taxon are pointed out. The second, Manaxius aurantiaca n. sp., is described based on a single female specimen from the Kaikata Seamount (at a depth of 299–335 m). It has rounded pleura of the pleomeres 2–5, and is notable in the lack of spines on the upper margin of the cheliped palms. In this regard, the new species closely resembles M. iro Poore, 2020. Differentiating characters between M. aurantiaca n. sp. and M. iro are discussed.